Identifying the failure-tolerant workspace boundaries of a kinematically redundant manipulator - Roberts, Rodney G., author; Jamisola, Rodrigo S., author; Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 2007)
In addition to possessing a number of other important properties, kinematically redundant manipulators are inherently more tolerant to locked-joint failures than nonredundant manipulators. However, a joint failure can still render a kinematically redundant manipulator useless if the manipulator is poorly designed or controlled. This paper presents a method for identifying a region of the workspace of a redundant manipulator for which task completion is guaranteed in the event of a locked-joint failure. The existence of such a region, called a failure-tolerant workspace, will be guaranteed by imposing a suitable set of artificial joint limits prior to a failure. Conditions are presented that characterize end-effector locations in this region. Based on these conditions, a method is presented that identifies the boundaries of the failure-tolerant workspace. Optimized failure-tolerant workspaces for a three degree-of-freedom planar robot are presented.
Keywords: end effectors; failure analysis; optimisation; redundant manipulators